(untitled) (Research, Society and Development, 2021)
Mental health is not dissociated from general health. Given the growth in the number of users with mental health disorders associated with the difficulty of early identification of this public by the health team, patient adherence to treatment, co-responsibility of the family and society’s openness to receive these users, there is a need for interventions in this area, such as qualification of the care process through the implementation of continuing education. This is an exploratory and descriptive study, of qualitative nature, type of experience report on the development of an operative plan. This work aims to qualify the Community Health Agents (CHAs) on the identification, reception and care of users with mental health disorders in the municipality of Duque Bacelar - MA. This project will promote permanent education with CHWs, working on the difficulties in identifying, welcoming and caring for users with mental health disorders. Therefore, it will favor the amplification of the listening, observation and perception acts of the CHWs in face of the demands that present mental problems, besides the development of skills and the awareness of the need for attitudes.